Parasympathetic modulation and running performance in distance runners - Boullosa, D. A.; Tuimil, J. L.; Leicht, A. S.; Crespo-Salgado, J. J. (The Journal of Strength and Conditioning Research, 2009)
This study examined the relationships between basal heart rate (BHR) and heart rate recovery (HRR), parasympathetic modulation parameters, with running performance in distance runners. It was hypothesized that greater parasympathetic modulation would be significantly associated with greater running performance. Twelve well-trained endurance runners (23.2 ± 3.3 years; 175.6 ± 5.8 cm; 65.2 ± 6.7 kg) performed the Université de Montréal Track Test (UMTT) until volitional exhaustion (total final time, TUMTT), with the highest completed stage recorded as the maximal aerobic speed (MAS). More than 48 hours afterwards, participants ran at the MAS until volitional exhaustion, with maximal running time (Tlim) recorded. Maximum heart rate was significantly greater for the UMTT compared with Tlim (p = 0.004). Significant correlations were exhibited between MAS and BHR (r = -0.845, p = 0.001); mean drop in heart rate at the first minute of recovery after the UMTT (r = 0.617, p = 0.033) and Tlim (r = 0.787, p = 0.002); and mean drop in heart rate at the second minute of recovery after the UMTT (r = 0.630, p = 0.028). These results support previous reports that endurance training results in greater running performance and greater parasympathetic modulation before and after exercise. We suggest that coaches consider HRR and BHR for the monitoring of training for endurance performance.